Treasure island - Stevenson, Robert Louis (Watertown Doyle Studio Press, 1996)
While going through the possessions of a deceased guest who owed them money, the mistress of the inn and her son find a treasure map that leads them to a pirate's fortune
Keywords: Tham khảo